Aco for Regression Testing By the Process Automated Slicing - Dhiman, Riza; Chopra, Vinay (International Journal of Computer Sciences and Engineering, 2025)
The Regression testing is used to retest the component of a system that verifies that after modifications. The test case prioritization is the technique of regression testing which prioritizes the test cases according to the changes which are done in the developed project. This work is based on automated and manual test case prioritization To test the new version of software test case prioritization is applied which prioritize the test cases according to changes and generate maximum number of faults. In this work, technique is been proposed which will traverse the DFD of the project and calculate the function importance which is calculated automated slicing. The functional importance values are given as input to hill climbing algorithm which prioritizes the test cases in the ascending or descending order according to function importance. The algorithm is performed in MATLAB and it is detect more faults in less time period